Angiogenic gene therapy does not cause retinal pathology. (September 2014) - Prokosch, Verena; Stupp, Tobias; Spaniol, Kristina; Pham, Emmanuel; Nikol, Sigrid
Abstract Background The potential negative influence of angiogenic gene therapy on the development or progression of retinal pathologies such as diabetic retinopathy (DR) or age‐related macular degeneration (AMD) has led to the systematic exclusion of affected patients from trials. We investigated the role of nonviral fibroblast factor 1 (NV1FGF) in two phase II, multinational, double‐blind, randomized, placebo‐controlled, gene therapy trials (TALISMAN 201 and 211). Methods One hundred and fifty‐two subjects with critical limb ischemia or claudication were randomized to receive eight intramuscular injections of 2.5 ml of NV1FGF at 0.2 mg/ml or 0.4 mg/dl or placebo. One hundred and fifty‐two patients received a plasmid dose of NV1FGF of up to 32 mg or placebo. All patients underwent a systematic ophthalmologic examination at baseline and at 3, 6 or 12 months following gene therapy. Twenty‐six of these patients (Münster subgroup) received a retinal fluorescence angiography at baseline and at final examination. Results Among those 26 patients, four of nine patients with diabetes suffered from nonproliferative DR. Three patients showed non‐exsudative AMD. No change of retinal morphology or function was observed in Münster subgroup of both TALISMAN trials independent of the intramuscular NV1FGF dosage applied. Conclusions Angiogenic gene therapy using NV1FGF is safe even in diabetics. Copyright © 2014 John Wiley & Sons, Ltd.